â€œPENERAPAN HUKUMANâ€, BIAS ANTARA UPAYA MENANAMKAN DISIPLIN DENGAN MELAKUKAN KEKERASAN TERHADAP ANAK - ARDINI, PUPUNG PUSPA (Jurnal Pendidikan Usia Dini, 2015)
Abstrac: This study aims to find out how to apply discipline to early childhood without punishment. Because without realizing through penalty adults, parents or teachers have been accused of abuses against children. Interactive data analysis models Milles and Huberman. This scientific study conducted in January 2015 in the village of West Java Ciangsana based assessment of the results of observation, documentation and literature related to discipline without punishing. The results showed that there are several key discipline without punishing. The main key is to teach discipline to the child not only to express but also give a concrete example to children. Keywords: Penalty, The Impact Of Punishment, Discipline Withoutpunishment